2013
DOI: 10.1371/journal.pone.0065670
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analyses of Streptococcus pseudopneumoniae Provide Insight into Virulence and Commensalism Dynamics

Abstract: Streptococcus pseudopneumoniae (SPPN) is a recently described species of the viridans group streptococci (VGS). Although the pathogenic potential of S. pseudopneumoniae remains uncertain, it is most commonly isolated from patients with underlying medical conditions, such as chronic obstructive pulmonary disease. S. pseudopneumoniae can be distinguished from the closely related species, S. pneumoniae and S. mitis, by phenotypic characteristics, including optochin resistance in the presence of 5% CO2, bile insol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 62 publications
(107 reference statements)
3
26
0
Order By: Relevance
“…Comparative genomic hybridization showed that this islet is common among S. pseudopneumoniae strains (13) and among eight sequence types of SMG that have been identified (14, 15). The sequence of lytA is S.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Comparative genomic hybridization showed that this islet is common among S. pseudopneumoniae strains (13) and among eight sequence types of SMG that have been identified (14, 15). The sequence of lytA is S.…”
Section: Introductionmentioning
confidence: 93%
“…An analysis of the first S. pseudopneumoniae genome of strain IS7493 documented the lack of some pneumococcal virulence factors, such as the capsule biosynthesis genes and the choline-binding proteins PspC, PcpA, and PspA (13). However, it contained the ply-lytA islet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roman numerals in column "ICE" refers to integration sites (Table S8). ICE, Mega-2 and "other resistances" refer to genotypic resistances; penicillin (Pen) and co-trimoxazole (SXT) refer to phenotypic resistances (Table S7) and references (5, 20, 57-59). ND, not determined due to the presence of pseudogenes/contig breaks; NA, data not available.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have described the presence of pneumococcal virulence genes in S. pseudopneumoniae (3, 9, 20, 21), but a comprehensive overview of the distribution of known, and potentially new, genes that could promote virulence and colonization in this species is lacking.…”
Section: Introductionmentioning
confidence: 99%